Theoretical aspects of charge correlations in θ-(BEDT-TTF)2X - Kazuhiko Kuroki (Science and Technology of Advanced Materials, 2009)
A review is given on the theoretical studies of charge correlations in θ-(BEDT-TTF)2X. Various studies show that within a purely electronic model on the θ-type lattice with on-site U and nearest neighbor Vp and Vc interactions, the diagonal stripe, c-axis three-fold, and the vertical stripe charge correlations are favored in the regime Vp<Vc, Vp~Vc, and Vp>Vc, respectively. In the realistic parameter regime of Vp~Vc, there is competition between the c-axis three fold state and diagonal stripe state. Since these are different from the experimentally observed a-axis three fold and the horizontal stripe charge correlations, additional effects have to be included in order to understand the experiments. The electron–lattice coupling, which tends to distort the lattice into the θd-type, is found to favor the horizontal stripe state, suggesting that the occurrence of this stripe ordering in the actual materials may not be of purely electronic origin. On the other hand, distant electron–electron interactions have to be considered in order to understand the a-axis three fold correlation, whose wave vector is close to the nesting vector of the Fermi surface. These studies seem to suggest that the minimal model to understand the charge correlation in θ-(BEDT-TTF)2X may be more complicated than expected. Future problems regarding the competition between different types of charge correlations are discussed.